Presence of Infected Gr-1intCD11bhiCD11cint Monocytic Myeloid Derived Suppressor Cells Subverts T Cell Response and Is Associated With Impaired Dendritic Cell Function in Mycobacterium avium-Infected Mice - Abdissa, Ketema; Nerlich, Andreas; Beineke, Andreas; Ruangkiattikul, Nanthapon; Pawar, Vinay; Heise, Ulrike; Janze, Nina; Falk, Christine; Bruder, Dunja; Schleicher, Ulrike; Bogdan, Christian; Weiss, Siegfried; et al. (Frontiers in Immunology, 2018)
Summary Myeloid-derived suppressor cells (MDSC) are immature myeloid cells with immunomodulatory function. Myeloid-derived suppressor cells (MDSC) are immature myeloid cells with immunomodulatory function. To study the mechanism by which MDSC affect antimicrobial immunity, we infected mice with two M. avium strains of differential virulence, highly virulent Mycobacterium avium subsp. avium strain 25291 (MAA) and low virulent Mycobacterium avium subsp. hominissuis strain 104 (MAH). Intraperitoneal infection with MAA, but not MAH, caused severe disease and massive splenic infiltration of monocytic MDSC (M-MDSC; Gr-1intCD11bhiCD11cint) expressing inducible NO synthase (Nos2) and bearing high numbers of mycobacteria. Depletion experiments demonstrated that M-MDSC were essential for disease progression. NO production by M-MDSC influenced antigen-uptake and processing by dendritic cells and proliferation of CD4+ T cells. M-MDSC were also induced in MAA-infected mice lacking Nos2. In these mice CD4+ T cell expansion and control of infection were restored. However, T cell inhibition was only partially relieved and arginases (Arg) 1-expressing M-MDSC were accumulated. Likewise, inhibition of Arg1 also partially rescued T cell proliferation. Thus, mycobacterial virulence results in the induction of M-MDSC that block the T cell response in a Nos2- and Arg1-dependent manner.